Pengaruh Tingkat Kehadiran Terhadap Hasil Belajar Statistik Mahasiswa - Lalu Saparwadi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
One way or another, a person's readiness to learn can be seen from the level of attendance at learning. At the higher education level, the presence of students in the learning process is very important. The aim of this research is to see the effect of attendance levels on student learning outcomes in statistics courses. Research is associative research which aims to determine the causal relationship between two or more variables. The sample in this research was 23 students. The research method in this research is the documentation method. The data analysis used in this research is quantitative data analysis with the help of SPSS 16. The results of this research show that there is an influence on student attendance levels on student learning outcomes in statistics courses. The influence of the level of student attendance on student learning outcomes is positive, where if the level of student attendance is good it will be in line with good student learning outcomes.